THE ALL CONQUERING LAMB: A comprehensive and devotional exposition of the book of Revelation - BRIAN. A. RUSSELL (Darlington Evangelical Press books, 2019)
The Bible s closing book, Revelation, is often neglected: apart from the imagery used in the book itself, there are the competing interpretations among sincere believers and then misuse by the cults. Brian Russell steers a safe course through these danger points. This is a book for the believer who loves the Word of God here you will find clear interpretation in agreement with a Reformed understanding of Scripture, accompanied by warm and encouraging application. All of this is written in a style that the ordinary believer will find attractive, but with sufficient depth to give the preacher help and guidance in bringing the message of Revelation to the church.